Cutting Technique For Constructing Small Radial Line Slot Array Antennas - Purnamirza, Teddy; Mohd Ibrahim, Imran; Susanti, Rika; Sutoyo; Mulyono; Radiles, Hasdi; Rahmi, Depriwana (Korean Institute of Electromagnetic Engineering and Science, 2021)
The design of small radial line slot array (RLSA) antennas requires more than simply decreasing the antenna radius, which leads to the problem of high reflection. To overcome this inconvenience, we introduce a technique for constructing small RLSA antennas with low reflection by cutting full-sized ones. We designed 42 ordinary full-size RLSA models with a radius of 75 mm and then cut them into 42 half RLSAs and 42 quarter RLSAs. The areas of the half RLSAs and the quarter RLSAs are equal to those of full-sized RLSAs with radii of 53 mm and 37 mm, respectively. Our results show that the gain of the quarter RLSA is less than that of the full RLSA by only 1 dB, whereas theoretically, the gain should decrease by 6 dB due to the size reduction. Interestingly, the gain of the half RLSAs is greater that of the full RLSA by 1 dB, whereas theoretically, a decrease of 3 dB was expected due to the size reduction. The half RLSA and the quarter RLSA also perform well in terms of reflection coefficient and bandwidth, thus demonstrating the efficacy of the cutting technique in constructing small low reflection RLSAs.